Pengembangan Kawasan Hutan Pinus Lahendong Sebagi objek Wisatadi Kota Tomohon - Tombeng, Marthen; Madea, Gloria (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2024)
The purpose of this research is to develop a strategy for developing the Hutan pinus Lahendong tourist attraction in realizing sustainable tourism. This research uses qualitative research methods. The data sources used in this research are primary data obtained through direct observation at the location including land use patterns, physical condition of the land, accommodation, condition of facilities and infrastructure as well as secondary data in the form of interview notes with tourists, the community and the government. Based on the research results, it was concluded that the natural tourist area of the Lahendong Pine Forest needs to be redeveloped by re-developing the area and repairing damaged facilities as well as adding facilities, this is done in order to support tourism progress and add added value. Lahendong pine forest tourist attraction.